Australia’s entrepreneurial spirit: the contribution of franchising - Bothams, Christopher M (Curtin University, 2008)
This research identifies the experiences, behaviours, attitudes, values and beliefs of Australia's most successful franchise owners in order to understand the reasons for their outstanding success in a business environment designed to encourage replication and uniformity. In this study, twelve of Australia's best franchisees have been interviewed to find out their personal qualities that have enabled them to succeed in the franchise business environment. A qualitative methodology within a constructivist ontology and interpretivist epistemology has been used. Interviews were conducted, coded, analysed and models developed using NVivo software. The coding and analysis led to the development of six key characteristics or behaviours of successful franchisees. Australia's best franchisees are successful because they are highly motivated, have outstanding business skills, are committed to franchising, demonstrate remarkable personal qualities reflected in highly ethical leadership with exceptional communication skills and create a business environment that has real customer focus. Human qualities are difficult to isolate and quantify. This research highlights those necessary to succeed in franchising and business generally. The findings from this research have been presented as a framework for franchisee success. The framework provides the basis of human characteristics and elements to consider in franchisee selection and business skill development. The title of this research is in many ways its conclusion. The contribution of franchising to Australia's entrepreneurial spirit is the growth and development of the business skills of franchisees, many of whom are entrepreneurs in the making.